Hata-Yanagiya physical activity calculation system: a novel global positioning system-based method for accurate estimation of oxygen consumption during walking and running - Hata, Keiichiro; Yanagiya, Toshio; Noro, Hiroaki; Suzuki, Yoshio (Frontiers in Sports and Active Living, 2025)
IntroductionMarathon running has become increasingly popular among amateur athletes, many of whom maintain speeds of 8–9 km/h. However, existing methods for estimating oxygen consumption (VO2) during running and walking—such as the American College of Sports Medicine (ACSM) equations and commercial activity monitors—often lack accuracy and transparency. This study introduces the Hata-Yanagiya Physical Activity Calculation (HYPAC) system, a novel approach for estimating VO2 using Global Positioning System (GPS) and map data.MethodsThe HYPAC system was developed through regression equations based on metabolic equivalents (METs) and slope data. To validate the system, 10 university students (5 runners, 5 non-runners) completed a 5 km course while equipped with a GPS device and a portable metabolic measurement system. VO2 estimates from the HYPAC system were compared with measured values and those calculated using ACSM equations.ResultsThe HYPAC system demonstrated high accuracy in estimating VO2, with a relative error of −0.03 [95% confidence intervals (CI): −0.14, 0.08] compared to measured values. For the running group, the HYPAC system achieved the lowest absolute mean relative error (0.02). In the mixed running/walking group, the HYPAC system maintained strong performance with a relative error of −0.07 (95% CI: −0.26, 0.12).DiscussionThe HYPAC system provides a transparent and accurate method for estimating VO2 during walking and running, outperforming existing methods under varied conditions. Its open-source framework encourages further validation and improvement by researchers and practitioners. Future studies should address limitations such as sample size and population diversity to enhance the system's applicability.